Brand Image, Harga, Lokasi, Desain dan Channel Distribution terhadap Keputusan Pembelian Properti di Citragrand Semarang - Sugiyanto, Yovita Natasia; Krisprimandoyo, D. Agung (IPM2KPE, 2024)
This study aims to identify factors that influence purchasing decisions in CitraGrand Semarang Housing, focusing on five variables: brand image, price, location, design, and distribution channels. The method used in this study is quantitative, with hypotheses tested through multiple linear regression analysis. The study population consisted of 1101 home and shophouse buyers in CitraGrand Semarang between September 2012 and October 2023. The sample taken was 92 respondents using stratified sampling techniques. Data were obtained through questionnaires distributed online and analyzed using SPSS 27.0 software. The results of the study indicate that simultaneously, brand image, price, location, design, and distribution channels have an influence on purchasing decisions. However, partially, only brand image and distribution channels have a positive effect, while price, location, and design do not affect purchasing decisions. The coefficient of determination shows that 37% of the variation in purchasing decisions can be explained by the five variables studied, while the remaining 67% is influenced by other factors not included in this study. Conclusion, Brand image and channel distribution are the main factors that influence property purchasing decisions in CitraGrand Semarang, while price, location, and design do not have a significant impact. This study suggests that developers should focus more on strengthening brand image and distribution strategies to increase purchasing decisions. Keywords: Brand Image, Channel Distribution, Design, Price, Purchasing Decisions